Student Learning Outcomes Through Integrated Pedagogical, Psychological and Health Education Approaches in Nigerian Universities - Boniface Sunday Akpan (WORLD JOURNAL OF INNOVATION AND MODERN TECHNOLOGY, 2026)
This study examined the influence of pedagogical approaches, psychological support services and health education on student learning outcomes in Nigerian universities in the South-South geopolitical zone of Nigeria. Three research questions were formulated for the study. Descriptive survey research design was adopted. The population comprised university lecturers, counsellors and health education personnel. Stratified random sampling technique was used to select respondents. Data were collected using a structured. The instrument was validated by three experts while reliability testing using Cronbach’s Alpha yielded a coefficient of 0.81. Data were analyzed using mean and standard deviation. Findings revealed that pedagogical approaches such as student-centred learning, ICT-based instruction and effective teaching strategies influence student learning outcomes, while large class size and poor teaching methods reduce academic performance. Results also showed that psychological support services affect students’ academic performance through stress, anxiety, burnout and counselling access. Findings further indicated that health education and student wellbeing influence learning outcomes through factors such as substance use, sleep patterns, nutrition and access to healthcare services. The study concluded that teaching practices, psychological wellbeing and health conditions jointly shape student learning outcomes. The researchers recommended the adoption of learner-centred teaching methods, strengthening counselling services and expansion of health education and student wellbeing programmes in Nigerian universities.